Penerapan Sistem Manajemen Mutu ISO 9001 dan Kontribusinya Bagi Pertumbuhan Gereja Pentakosta di Cililitan - Simamora, Parasian; Nugroho, Andreas Eko; Jonathans, Kornelius Rulli (Jurnal Teologi dan Pelayanan Kerusso, 2025)
This study aims to analyze the implementation of the ISO 9001 quality management system at the Pentecostal Church of Cililitan, which has faced a decline in congregation numbers in recent years. Effective and systematic management of church services is crucial to meet the spiritual needs of the congregation and to have a positive impact on society. Specifically, the decline in the number of congregants is caused by issues of ineffective leadership and poor internal communication. The research employs a qualitative approach with a case study method. Data was collected through in-depth interviews with church leaders, service staff, and congregation members, as well as document analysis related to the implementation of ISO 9001. A literature review was also conducted to understand how the quality management system can be applied in the context of religious organizations. The results of the study show that the implementation of ISO 9001 has made a positive contribution to the church’s organizational structure, including improvements in work procedures, enhanced internal communication, and strengthened leadership. The implementation of this system has helped create a more organized service environment, increased congregational satisfaction, and restored trust in the church leadership. However, the success of implementing this quality management system depends heavily on the commitment of the church leadership and the active involvement of all members of the organization. The conclusion of this study emphasizes that the implementation of ISO 9001 can significantly contribute to the growth of the church. With consistent implementation, the church can improve service quality and experience sustainable growth in the congregation. This study recommends that the church continue to strengthen leadership and communication aspects as part of the strategy to enhance service quality.